Smart Card in Fun Learning Activity to Increase Interest in English Grammar Learning - Ratih Laily Nurjanah; Mochamad Rizqi Adhi Pratama (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2019)
Learning English in the classroom, especially grammar courses, is often considered a boring subject because the learning and teaching process is often done monotonously. The Smart Card Learning Model is expected to be able to provide a different atmosphere in the grammar class. At the stage of initiation, introduction, and application, it is expected that this learning model can increase students' interest and enthusiasm in learning grammar. From that point, increasing student interest and enthusiasm is expected to have implications for increasing student grades. This study aims to answer the 3 research problems: 1)What are the difficulties faced by students in Intermediate English Grammar class?, 2)What are the students perception on Smart Card?, 3)How can Smart Card help students in Grammar?. From the results of the research that has been carried out, students faced the difficulties in memorizing 16 tenses and the boredom in the class related to activities given by the lecturer. Students found Smart Cards was very fun, easy to use and increase students’ interest in learning English Grammar. The majority of students want a variety of learning media besides the media commonly used by lecturers such as power points, lectures, and group discussions.